The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1215/00703370-10604036
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Family Member Deaths Across the Life Course for Hispanic Individuals

Abstract: The present study documents differences in exposure to family member deaths among foreign-born and U.S.-born Hispanic individuals compared with non-Hispanic Black and non-Hispanic White individuals. We use data from the Health and Retirement Study (HRS; 1992–2016, ages 51+; N = 23,228) and the National Longitudinal Study of Adolescent to Adult Health (Add Health; Waves I–V, ages 12–43; N = 11,088) to estimate the risk of exposure to the death of a mother, father, spouse, sibling, and child across the life cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…Moreover, while it is not a limitation for this study, sociodemographic differences in the effect and pathways should be considered for future research. Prior research has shown that Black and Latinx individuals are more likely to experience parental death in early life than White individuals ( Donnelly et al, 2023a ; Umberson et al, 2017 ). Women may have greater risk of poorer health outcomes than men from parental loss in childhood ( Liu et al, 2022a , Liu et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, while it is not a limitation for this study, sociodemographic differences in the effect and pathways should be considered for future research. Prior research has shown that Black and Latinx individuals are more likely to experience parental death in early life than White individuals ( Donnelly et al, 2023a ; Umberson et al, 2017 ). Women may have greater risk of poorer health outcomes than men from parental loss in childhood ( Liu et al, 2022a , Liu et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…The death of a parent in early life should be viewed as an important juncture in a young person's life that has the potential to cascade into a lifetime of hardship as evidenced by worse mental health, compromised physical health, and elevated mortality risk ( Donnelly et al, 2023a ; Liu et al, 2022a ; Smith, 2014 ). We provide evidence that parental death in early life is associated with epigenetic changes that underlie several poor age-related health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address existing gaps, we investigated if familial loss and quantity of loss, occurring either in early life or adulthood, were associated with biological aging in a diverse, population-based sample. Acknowledging prior research on racial disparities in loss experiences and variability in exposure histories, 6 , 14 we also examined the interaction between loss and race on biological aging. We analyzed survey responses from waves 1 to 5 of the National Longitudinal Study of Adolescent to Adult Health (Add Health), coupled with new epigenetic data from wave 5.…”
Section: Introductionmentioning
confidence: 99%